Clogging effect of prefabricated horizontal drains in dredged soil by air booster vacuum consolidation. Issue 6 (December 2021) - Hu, Xiuqing; Zhang, Weikai; Fu, Hongtao; Wang, Jun; Ni, Junfeng
Abstract: The typical problem that occurs when the conventional vacuum preloading (CVP) method is applied to dredged soil is that the drainage is impeded, permeability is progressively reduced, and clogging occurs in prefabricated horizontal drains (PHDs). This paper proposes a method in which air booster through PHDs under vacuum preloading to reinforce newly dredged soil, and thereby solve the clogging problem. To evaluate the proposed method, several experiments were conducted using soils with variable degrees of consolidation and the effect on clogging determined. Furthermore, the proposed method was compared to the CVP method considering several variables monitored during consolidation and after consolidation. The results indicate that the proposed method is superior to the CVP as it more effectively alleviates the clogging problem. These findings could provide design criteria for dredged soil consolidation in similar projects and for scientific research and engineering practice. Highlights: An air pressurization method is proposed for prefabricated horizontal drains (PHDs). The proposed method effectively alleviates the clogging problem in PHDs. Results show that it is superior to the conventional vacuum preloading (CVP) method. The optimum pressurising activation condition is at soil degree of calculation of 50%. Findings can provide dredged soil consolidation design criteria for similar projects.